MASS TRANSFER IN CLEANING OF HYDROGEN FLUORIDE GAS IN FILTER APPARATUS - Akmaljon Akhrorov (American Journals Publishing, 2023)
In the article, mass transfer process which is occurred as the result of liquid drops motion in the gas flow was studied. Furthermore, absorption of the hydrogen-fluoride component dusty gas in soda ash drops was searched. Consequently, influence of gas velocity and liquid flow to the mass transfer coefficient and purification efficiency of the rotary-filter gas cleaner in its different kind of filters and liquid injection nozzles was studied experimentally. In order to carry out a process effectively optimal quantities of changeable parameters that’s liquid flow and gas velocity were recommended.
Keywords: Rotary-filter, dusty gas, hydrodynamic, mass transfer, mass transfer coefficient, liquid flow, gas velocity, filtration layer.